Creating Interconnected Outdoor Green Infrastructure in The Case of Aksum Historical Sites, Ethiopia - Gebru, Guesh Hagos (CSID Journal of Infrastructure Development, 2023)
This study investigates the state of outdoor green infrastructures (GI) in Aksum, Ethiopia, employing qualitative and quantitative approaches to address the disconnect between the expanding urban fabric and sustainable green space development. Sentinel satellite imagery and public perception surveys revealed a fragmented landscape of green spaces, including underdeveloped areas like heritage sites, cemeteries, churches, public spaces, stream fronts, and roadside spaces. Quantitative analysis using the Normalized Difference Vegetation Index (NDVI) and Normalized Difference Built-Up Index (NDBI) indicated limited healthy vegetation and a built environment predominance. NDVI values ranged from +0.1 to +0.5, suggesting the presence of grass and shrubs, while NDBI results varied between 0 and 0.252, reflecting low vegetative cover. Furthermore, the Built-Up (BU) index in residential zones ranged from -0.644 to +0.128, underscoring the poor condition of GIs and their lack of interconnectivity. Addressing these issues, the research proposes a conceptual design for an interconnected GI, integrating various urban spaces into a cohesive green network. This design aims to remedy the fragmentation and enhance the environmental, social, and economic aspects of urban life in Aksum.